PEMBELAJARAN KREATIF BERBASIS STUDENT CENTERED LEARNING PADA ELEKTRONIKA DASAR I MELALUI MODEL PROBLEM BASED LEARNING - Makhrus, Muh; Wahyudi, Wahyudi (Universitas Hamzanwadi, 2020)
This study aims to measure the ability of soft skills and hard skills of students after attending Elementary Electronics learning through creative learning based on student-cantered learning with problem-based learning models. Research subjects in this study were 25 students of the physics education program University of Mataram. This type of research is a qualitative descriptive and assessment of the ability of soft skills and hard skills carried out by 2 observers based on the assessment of soft skills and hard skills assessment instruments when learning Elementary Electronics is ongoing. Based on the results of the study, learning Basic Electronics I based on student centered learning with problem based learning models combined with the use of livewire 1.1 Pro including learning that can increase student activity. This learning can increase student soft skills and hard skills up to 85% which is included in the very high category